The properties on differential-difference polynomials - Cao, T. B.; Liu, K.; Liu, X. L. (Ukrains’kyi Matematychnyi Zhurnal, 2017)
The main aim of this paper is to improve some classical results on the distribution of zeros for differential polynomials anddifferential-difference polynomials. We present some results on the distribution of zeros of $[f(z)^nf(z + c)]^{(k)} α (z)$ and$[f(z)^n(f(z + c) f(z))]^{(k)} α (z)$ and give some examples to show that the results are best possible in a certain sense.